Isometric contraction force measurement of hiPSC-CMs on a movable plate with a feedback-controlled MEMS cantilever probe. (2nd August 2021) - Matsudaira, Kenei; Takahashi, Hidetoshi; Hirayama-Shoji, Kayoko; Tsukagoshi, Takuya; Nguyen, Thanh-Vinh; Shimoyama, Isao
Abstract: We propose a measurement method with a feedback system to evaluate the contraction forces of human iPS cell-derived cardiomyocytes (hiPSC-CMs) in a dynamic mechanical environment. The measurement of the hiPSC-CM contraction forces is important for regenerative medicine; however, conventional methods are not able to evaluate these forces when the cells are subjected to a dynamic load similar to that from the heart. The proposed measurement system is composed of a micromachined piezoresistive cantilever attached to a feedback-controlled piezo stage and a micromachined movable plate where cells are cultured. A high sampling rate (2 kHz) and real-time control of the cell length were realized via the feedback-controlled piezo stage, while the contraction forces were measured by the cantilever. We evaluated the contraction forces of hiPSC-CMs in conditions of isometric and auxotonic contractions. Due to feedback-controlled loading for isometric contraction, the cell shrinkage was controlled to be less than 200 nm. Auxotonic contraction forces of 3.9 μN were measured without feedback control, while the contraction forces of isometric contraction were 6.0 μN with feedback-controlled loading. The results showed that the method leads to a work-loop evaluation of the hiPSC-CM cardiac cycle.